(untitled) (Journal of Hama University, 2024)
The research aims to evaluate the effect of applying micro-osteoperforation technique to accelerate decrowding of lower incisors (without extraction) treated with clear aligners on patients’ pain, discomfort and their levels of acceptance of this technique. The research sample consisted of (36) patients with a mean age of (22.26±1.34) years. They were randomly distributed either to the micro-osteoperforation group or to the control group with an allocation ratio of (1:1). The lower incisors of patients in both groups were decrowded with clear aligners, and before applying the first clear aligner to patients in the micro-osteoperforation group, 14 cortical perforations were made, two perforations in each interdental space of the lower incisors from the buccal aspect. The diameter of each perforation was 1.2 mm, and its depth was 1 mm within the cortical bone using a lance drill after making adjustments to it. Patients in both groups were asked to record their pain and discomfort levels by filling out a questionnaire with a 100-mm Numeric Rating Scale (NRS) after one, two, and three days of orthodontic treatment initiation (after first clear aligner application). An additional questionnaire was delivered to the micro-osteoperforation group patients after one month which contains questions regarding their acceptability of the surgical procedure. No statistically significant differences were found in pain and discomfort levels between the two groups in each studied time point (P-value > 0.05). Furthermore, patients accepted the surgical procedure. Micro-osteoperforations technique applied to orthodontic treatment with clear aligners in order to accelerate decrowding of lower incisors (without extraction) is a well-tolerated technique with levels of pain and discomfort similar to that of the orthodontic treatment with clear aligners only.